ИЖТИМОИЙ ЖАРАЁНЛАРНИНГ МУРАККАБ ХУСУСИЯТЛАРИНИНГ НАЗАРИЙ – ФАЛСАФИЙ ТАҲЛИЛИ - Алланазарова, Б.А. (SCIENCE and SOCIETY, 2021)
This article explores the theoretical and philosophical features of the complexity of social processes, such as nonlinearity, uncertainty, chaotic, social bifurcation.